FOUNDATION AND RETAINING WALL DESIGN OF GEDEBAGE BANDUNG CONTEMPORARY FINE ART MUSEUM - SUFARI (NIM: 15014060), FADIL
Bandung contemporary fine arts museum located in the Gedebage area of Bandung city has 5 floors and 2 basement floors. In its planning, the foundation system will be designed and the retaining wall used diaphragm wall with anchor reinforcement for the basement structure. The foundation used is the bored pile foundation using 2 types of borehole for the calculation of foundations namely BH 1&6 and BH 7. The dimensions of the bored pile used are 800 mm, 1000 mm, and 1200 mm. The axial bearing capacity determined by using manual calculations based on Meyerhoff which refers to the load of Allowable Stress Design (ASD). The calculation of lateral bearing capacity and pile group bearing capacity determined by using LPILE and GROUP PILE software. There are 16 types of pile cap which its length varies from 12 m, 13 m, 14 m, 15 m, and 23 m based on configuration calculations and the efficiency of the pile group. The total settlement produced is still within the permit limit, while the calculation on differential settlement is obtained by settlement between the pile cap exceeding the permit limit, so it is necessary to design a tie beam between the pile cap. Diaphragm wall is designed to protect excavation in the basement. The analysis was calculated using PLAXIS 2D software according to the construction stage. The construction stage is 1 stage installation of diaphragm wall, 4 stages of excavation, and 2 stages of installation of ground anchor at elevation of -2 m, and -6 m. The required wall thickness is 0.8 m and 30 meters deep. The prestressing force applied to the ground anchor is 558 kN / m and 781.2 kN / m. The reinforcement design of foundation and diaphragm wall refers to the regulation of SNI 2847-2013 about The Planning and Designing of Concrete Structures for Bulding Construction.